The association of financial resources and loneliness among older adults during a state of emergency. - Madeleine Drost; Cäzilia Loibl; Anastasia Snyder; Michael Betz (PLoS ONE)
This study focuses on the initial wave of the COVID-19 pandemic in Spring 2020 in the United States to assess how liquidity constraints were related to loneliness among older adults. Data are from the COVID Impact Survey, which was used to collect data in April, May and June 2020 across the U.S. (n = 5,664). We use means comparison tests and linear regressions and find that emergency savings, rather than household income, predict loneliness among older adults during the initial COVID-19 wave. Emergency savings, especially enough to avoid using credit cards, was most predictive of older adult loneliness levels. Income and access to emergency savings did not influence the relationship between actions taken and personal plans changed as a result of COVID-19. Easing lockdown restrictions was unrelated to the relationship between loneliness and liquidity constraints, actions taken and personal plans changed due to the COVID-19 pandemic. Findings suggest that, in the early months of the COVID-19 pandemic, loneliness associated with the actions taken to avoid COVID-19 and personal plans changed was experienced across all socio-economic groups of older adults in this sample in similar ways, regardless of income levels and wealth. In addition, a better understanding of loneliness in older age during the COVID-19 pandemic may require a fuller analysis of households' financial situation beyond income, and points to the central role of credit card debt for loneliness in older age.